Examination and implementation for direct torque controlled permanent magnet synchronous motor with space vector modulation. (February 2019) - Ning, Bowen; Cheng, Shanmei; Yan, Baokang; Zhou, Fengxing
This study investigates the direct torque control strategy of permanent magnet synchronous motor with the space vector modulation, on account of large torque fluctuation and varied switching frequency of classic direct torque control strategy. The relationship among the terminal control voltages and the torque and stator flux of the permanent magnet synchronous motor is derived through the dynamic model of motor. Accordingly, the torque and the flux closed-loop feedback control structure are established, where the error signals are regulated by the proportional and integral controllers to generate output voltages. Furthermore, the parameters of the controllers are designed through explicitly analyzing the frequency domain models of the torque control loop and the flux control loop. The accurate calculation formula of control parameters, which has both explicit setting target and definite physical meaning, is obtained. Therefore, the design of torque and flux controller parameters becomes easy in the direct torque control with space vector modulation technology, and satisfactory flux and torque control can be acquired. Finally, simulation and experimental tests are demonstrated in support of the validity of the investigated scheme and the feasibility of the proposed controller parameter design.